Participatory Learning in the Utilization of Social Media: A Study on PIK-R Well Majalaya in Child Marriage Prevention Education - Nudiati, Deti; Sukmana, Cucu; Darmawanti, Irma; Mutamam, Muhamad Hadi Ali; Alamsyah, Bangkit; Jalane, Mildrett de Fatima (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2026)
Child marriage is still a serious issue in Indonesia that has an impact on reproductive health, education, and the quality of life of adolescents. This study aims to analyze the digital strategy of the Well Majalaya Youth Information and Counseling Center (PIK-R Well) for its Instagram campaign to prevent child marriage. Data were collected through analysis of 10 Instagram posts from June-July 2025 and through a Focus Group Discussion (FGD) with PIK-R Well administrators, using the Kolb Experiential Learning approach. The results showed that event-themed and collaborative posts had wide reach, but more meaningful engagement came from factual educational content, albeit with fewer views. Through the FGD, PIK-R Well administrators reflected on their experiences, identified weaknesses in previous digital strategies, and formulated new strategies, including increasing the frequency and variety of content, using a call to action (CTA), and fostering digital collaboration with schools and communities. This study concludes that social media can serve not only as a promotional tool but also as an experiential learning space that strengthens organizational capacity and increases adolescents’ awareness of the dangers of child marriage.